Gamification of Digital Gaming – Video Game Competitions and High Score Tables as Prehistory of E-Sports in Finland in the 1980s and Early 1990s - Saarikoski Petri; Suominen Jaakko; Reunanen Markku (Finland, 2022)
The aim of this paper is to examine the “prehistory” of E-sports from the Finnish perspective. In the
context of the GamiFIN conference, we approach E-sports as a gamified form of video gaming. In particular, we
study the early Finnish game championships of the 1980s and the early 1990s as well as the high score lists of
Finnish computer and video game magazines. We ask the question: how did these publications and activities
construct video gaming as a socially-experienced competitive practice? In addition, we seek answers to the
following questions: Who were the early video game contestants? How was competitive gaming presented in
media? What kind of rules were defined for the contests? How was cheating dealt with?
Keywords: Competitive gaming, game history, e-sports, high score tables, Pac-Man
Proceedings of the 1st International GamiFIN Conference, Pori, Finland, May 9-10, 2017